Removal of Orange II (OII) dye by simulated solar photoelectro-Fenton and stability of WO2.72/Vulcan XC72 gas diffusion electrode. (January 2020) - Paz, Edson C.; Pinheiro, Victor S.; Joca, Jhonny Frank Sousa; de Souza, Rafael Augusto Sotana; Gentil, Tuani C.; Lanza, Marcos R.V.; de Oliveira, Hueder Paulo Moisés; Neto, Ana Maria Pereira; Gaubeur, Ivanise; Santos, Mauro C.
Abstract: The objectives of this study were to determine the viability of removing Orange II (OII) dye by simulated solar photoelectro-Fenton (SSPEF) and to evaluate the stability of a WO2.72 /Vulcan XC72 gas diffusion electrode (GDE) and thus determine its best operating parameters. The GDE cathode was combined with a BDD anode for decolorization and mineralization of 350 mL of 0.26 mM OII by anodic oxidation with electrogenerated H2 O2 (AO-H2 O2 ), electro-Fenton (EF) and photoelectro-Fenton (PEF) at 100, 150 and 200 mA cm −2 and SSPEF at 150 mA cm −2 . The GDE showed successful operation for electrogeneration, good reproducibility and low leaching of W. Decolorization and OII decay were directly proportional to the current density (j). AO-H2 O2 had a reduced performance that was only half of the SSPEF, PEF and EF treatments. The mineralization efficiency was in the following order: AO-H2 O2  < EF < PEF ≈ SSPEF. This showed that the GDE, BDD anode and light radiation combination was advantageous and indicated that the SSPEF process is promising with both a lower cost than using UV lamps and simulating solar photoelectro-Fenton process. The PEF process with the lowest j (100 mA cm −2 ) showed the best performance-mineralization current efficiency. Highlights: Removal of Orange II (OII) dye by simulated solar photoelectro-Fenton SSPEF. The GDE showed successful operation and low leaching of W. The mineralization efficiency was in the order: AO-H2 O2  < EF < PEF ≈ SSPEF. SSPEF process is promising with a lower cost than using UV lamps.